The influence of deformation path on strain characteristics of AA1050 aluminium processed by equal-channel angular pressing followed by rolling - Vega, M. C. V. (2015)
The present investigation reports on the microstructure evolution, texture development, the nature of the grain boundaries and the tensile and deep drawing behaviour of commercial AA1050 Al processed by Equal Channel Angular Pressing (ECAP) plus rolling. Although in terms of final mechanical strength ECAP and rolling are indistinguishable, the deformation path is substantially different, and this has important consequences on both microstructure and texture. From the spatial distribution of high angle grain boundaries (HAGB) and low angle grain boundaries (LAGB), the fine microstructure and the crystallographic texture, it was concluded that the microstructure is oriented according to the external imposed flow: a spin movement in the ECAP process, which promotes the rotation of the cells inside the original grain, followed by a sliding movement caused by the rolling, leading to grain elongation. The ECAP process is more suitable to promote a higher fraction of HAGBs, and the same time as it reduces the intensity of the bulk crystallographic texture. As a consequence an increase of the penetration depth and deformation strain, as measured by the Erichsen test, was observed in samples processed by 8 ECAP passes, characterized by low texture intensity and a high degree of dynamic recrystallization.